Antifungal Activity of Bacterial Isolates from Straw Mushroom Cultivation Medium against Phytopathogenic Fungi - Masrukhin Masrukhin; Ade Lia Putri; Tri Ratna Sulistiyani; Muhammad Ilyas; Ismu Purnaningsih; Iwan Saskiawan; Muhammad Yusrun Niam (Universitas Gadjah Mada, 2021)
Several bacteria were isolated from straw mushroom (Volvariella volvacea) cultivation medium. There are three potential isolates previously characterized and has growth inhibition effect against V. volvacea. This screening result lead to the further study about the inhibition activity against phytopathogenic fungi. The aim of this research is to investigate the antifungal activity of three bacterial isolates against three phytopathogenic fungi and identification of the bacteria. The method used in this study are antifungal assay using co-culture method and disk difussion assay using the filtrate of each bacteria. The profile of antifungal compound was identified using ethyl acetate extract followed by evaporation and gas chromatography (GC-MS) analysis. Identification of each isolates was performed using 16S rDNA amplification and sequencing. Three phytopathogenic fungi i.e Cercospora lactucae (InaCC F168), Colletotrichum gloeosporides (InaCC F304) and Fusarium oxysporum f.sp. cubense (F817) were co-cultured with bacterial isolates C2.2, C3.8, and D3.3. The C3.8 isolate has highest average inhibition activity either using isolate and filtrate. The result relatively consistent against three phytopathogenic fungi. The metabolite profile of C3.8 isolate showed the Bis(2-ethylhexyl) phthalate as the main compound with 97% similarity. Bis(2-ethylhexyl) phthalate has potential effect as antibacterial and antifungal compound. According to EzBioCloud and GeneBank databases, the C2.2 isolate identified as Bacillus tequilensis, C3.8 as Bacillus siamensis and D3.3 as Bacillus subtilis subsp. Subtilis. This study also shows the potential of Bacillus siamensis C3.8 as biocontrol against phytopathogenic fungi.